Physical–numerical parameters in laminar simulations of natural convection on three-dimensional square plates - Verdério Júnior, Sílvio Aparecido; Scalon, Vicente Luiz [UNESP]; Oliveira, Santiago del Rio [UNESP] (Emerald, 2021)
Purpose: The purpose of this study is to analyze the influence of the main physical–numerical parameters in the computational evaluation of natural convection heat transfer rates in isothermal flat square plates in the laminar regime. Moreover by experimentally validate the results of the numerical models and define the best parameter settings for the problem situation studied. Design/methodology/approach: The present work is an extension of the study by Verderio Junior et al. (2021), differing in the modeling, results analysis and conclusions for the laminar flow regime with (Formula presented.). The analysis of the influence and precision of the physical–numerical parameters: boundary conditions, degree of mesh refinement, refinement layers and κ – ω SST and κ – ε turbulence models, occurred from the results from 48 numerical models, which were simulated using the OpenFOAM® software. Comparing the experimental mean Nusselt number with the numerical values obtained in the simulations and the analysis of the relative errors were used in the evaluation of the advantages, restrictions and selection of the most adequate parameters to the studied problem situation. Findings: The numerical results of the simulations were validated, with excellent precision, from the experimental reference by Kitamura et al. (2015). The application of the κ – ω SST and κ – ε turbulence models and the boundary conditions (with and without wall functions) were also physically validated. The use of the κ – ω SST and κ – ε turbulence models, in terms of cost-benefit and precision, proved to be inefficient in the problem situation studied. Simulations without turbulence models proved to be the best option for the physical model for the studies developed. The use of refinement layers, especially in applications with wall functions and turbulence models, proved unfeasible. Practical implications: Use of the physical–numerical parameters studied and validated, and application of the modeling and analysis methodology developed in projects and optimizations of natural convection thermal systems in a laminar flow regime. Just like, reduce costs and the dependence on the construction of experimental apparatus to obtain experimental results and in the numerical-experimental validation process. Social implications: Exclusive use of free and open-source computational tools as an alternative to feasible research in the computational fluid dynamics area in conditions of budget constraints and lack of higher value-added infrastructure, with applicability in the academic and industrial areas. Originality/value: The results and discussions presented are original and new for the applied study of laminar natural convection in isothermal flat plate, with analysis and validation of the main physical and numerical influence parameters.
Keywords: Heat transfer; Laminar regime; Natural convection; Numerical validation; OpenFOAM®